Quad 3.0 : Japan, Indo-Pacific and minilateralism - Koga, Kei (2022)
Japan under the first and second Abe administration in 2006–07 and 2012–20, respectively, played a pivotal leading role in creating and institutionalising the Quad. While Japan has taken on a more supportive role in the post-Abe administrations, there are unique roles that Japan could still play in coordinating and shaping the strategic role of the Quad, such as configuring its institutional relations with the Association of Southeast Asian Nations (ASEAN).